Analysis of Seismic Fragility Functions of Highway Embankments - Hübner, Balázs; Mahler, András (Periodica Polytechnica Civil Engineering, 2020)
Vulnerability assessment of structures is a vitally important topic among earthquake engineering researchers. Generally, their primary focus is on the seismic performance of buildings. Less attention is paid to geotechnical structures, even though information about the performance of these structures (e.g. road embankments, levees, cuts) during an earthquake is essential for planning remediation and rescue efforts after disasters. In this paper the seismic fragility functions of a highway embankment are defined following an analytical methodolgy. The technique is a displacement-based evaluation of seismic vulnerability. Displacements of an embankment during a seismic event are approximated by a 2-D nonlinear ground response analysis using the finite element method. The numerical model was calibrated based on the results of a 1-D nonlinear ground response analysis. The expected displacements were calculated for 3 different embankment heights and Peak Ground Acceleration (PGA) values between 0,05 and 0,35g. Based on the results of the 2-D finite element analysis, the relationship between displacements and different seismic intensity measures (PGA, Arias-intensity) was investigated. Different damage states were considered, and the probability of their exceedance was investigated. The seismic fragility functions of the embankments were developed based on probability of exceedance of these different damage states based on a log-normal fragility function. The legitimacy of using a log-normal fragility function is also examined.